Implementation of PAI Learning Design in Developing Religious Tolerance in Public High Schools - Maarif, Muhammad Anas; Muarofah, Siti Lailatul; Sianipar, Godlif; Hariyadi, Ahmad; Kausar, Shakila (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This article aims to describe and analyze the urgency and implementation of PAI learning design in developing religious tolerance at SMA Negeri 1 Kedamean Gresik. The research method used in this article is qualitative with a case study approach. Data collection techniques using interviews, observation, and documentation. The results of the research are that there are 3 stages in the implementation of PAI learning design in developing religious tolerance at SMA Negeri 1 Kedamean, namely planning, implementation, and evaluation. This research can help increase students' understanding of other religions so that they are able to respect differences in beliefs. This research can provide learning experiences that can help students develop empathy towards individuals from various religious backgrounds. By understanding the values of tolerance, students can be better able to prevent religious discrimination in society. Religious tolerance education needs to be given to students as early as possible. Instilling openness of thought from an early age, and accepting differences based on the values of tolerance, will of course minimize attitudes of intolerance in students.